Specific spatio-temporal dynamics of absorptive fine roots in response to neighbor species identity in a mixed beech–spruce forest. (22nd August 2019) - Zwetsloot, Marie J; Goebel, Marc; Paya, Alex; Grams, Thorsten E E; Bauerle, Taryn L
Abstract: Absorptive fine roots are an important driver of soil biogeochemical cycles. Yet, the spatio-temporal dynamics of those roots in the presence of neighboring species remain poorly understood. The aim of this study was to analyze shifts in absorptive fine-root traits in monoculture or mixtures of Fagus sylvatica [L.] and Picea abies [L.] Karst. We hypothesized that root competition would be higher under single-species than mixed-species interactions, leading to changes in (i) root survivorship, diameter and respiration and (ii) spatio-temporal patterns of root growth and death. Using minirhizotron methods, we monitored the timing and location of absorptive fine-root growth and death at an experimental forest in southern Germany from 2011 to 2013. We also measured root respiration in the spring and fall seasons of 2012 and 2013. Our findings show that the absorptive fine roots of F. sylvatica had a 50% higher risk of root mortality and higher respiration rates in the single-species compared to mixed-species zones. These results support our hypothesis that root competition is less intense for F. sylvatica in mixture versus monoculture. We were unable to find confirmation for the same hypothesis for P. abies . To analyze spatio-temporal patterns of absorptive fine-root production and mortality, we used a mixed-effects model considering root depth (space) and seasons (time) simultaneously. This analysis showed that F. sylvatica shifts root production towards shallower soil layers in mixed-species stands, besides significant seasonal fluctuations in root production depths for both species. Ultimately, the impact of neighbor species identity on root traits observed in this study has important implications for where, when and how fast root-facilitated carbon cycling takes place in single-species versus mixed-species forests. In addition, our study highlights the need for inclusion of absorptive fine-root spatio-temporal dynamics when examining belowground plant interactions and biogeochemical cycles.